The longevity of broadleaf deciduous trees in Northern Hemisphere temperate forests: insights from tree-ring series - Di Filippo, Alfredo; Pederson, Neil; Baliva, Michele; Brunetti, Michele; Dinella, Anna; Kitamura, Keiko; Knapp, Hanns D.; Schirone, Bartolomeo; Piovesan, Gianluca (Frontiers in Ecology and Evolution, 2015)
Understanding the factors controlling the expression of longevity in trees is still an outstanding challenge for tree biologists and forest ecologists. We gathered tree-ring data and literature for broadleaf deciduous (BD) temperate trees growing in closed-canopy old-growth forests in the Northern Hemisphere to explore the role of geographic patterns, climate variability, and growth rates on longevity. Our pan-continental analysis, covering 32 species from 12 genera, showed that 300-400 years can be considered a baseline threshold for maximum tree lifespan in many temperate deciduous forests. Maximum age varies greatly in relation to environmental features, even within the same species. Tree longevity is generally promoted by reduced growth rates across large genetic differences and environmental gradients. We argue that slower growth rates, and the associated smaller size, provide trees with an advantage against biotic and abiotic disturbance agents, supporting the idea that size, not age, is the main constraint to tree longevity. The oldest trees were living most of their life in subordinate canopy conditions and/or within primary forests in cool temperate environments and outside major storm tracks. Very old trees are thus characterized by slow growth and often live in forests with harsh site conditions and infrequent disturbance events that kill much of the trees. Temperature inversely controls the expression of longevity in mesophilous species (Fagus spp.), but its role in Quercus spp. is more complex and warrants further research in disturbance ecology. Biological, ecological and historical drivers must be considered to understand the constraints imposed to longevity within different forest landscapes.